Analysis of Factors Influencing Farmers' Interest in Using Combine Harvesters in Lumajang Regency - Singgih Setyo Utomo*; Cakti Indra Gunawan; Budi Santoso (Riwayat: Educational Journal of History and Humanities, 2024)
Lumajang is one of the districts in East Java where the majority of farmers grow rice. One of the causes of the decrease in productivity is due to the delay in harvest time due to the lack of rice harvesting labor and the type of harvesting machine used is inefficient. The purpose of this study is to measure the factors that influence farmers' interest in using Combine Harvester. The sample needed in this study is 93 respondents. The data analysis technique used is descriptive quantitative analysis using Structural Equation Modelling Partial Least Square (SEM-PLS). There are four exogenous variables, including the characteristics of farming, counseling and information, farmer characteristics, and the role of credit. The results of the study show that there are three factors that have a significant influence on farmers' interest, namely innovation, behavior control and attitude. The most significant result was the attitude factor with a P value of 0.012. Meanwhile, the factor that does not have a significant effect is the subjective norm.